De Novo Donor Specific Antibody and Long-Term Outcome After Liver Transplantation: A Systematic Review and Meta-Analysis - Zahra Beyzaei; Bita Geramizadeh; Bita Geramizadeh; Zahra Bagheri; Sara Karimzadeh; Alireza Shojazadeh (Frontiers in Immunology, 2020)
BackgroundThe impact of de novo anti-HLA donor-specific alloantibodies (DSA) which develop after long-term liver transplantation (LT) remains controversial and unclear. The aim of this study was to investigate the role of de novo DSAs on the outcome in LT.MethodsWe did a systematic review and meta-analysis of observational studies published until Dec 31, 2019, that reported de novo DSA outcome data (≥1 year of follow-up) after liver transplant. A literature search in the MEDLINE/PubMed, EMBASE, Cochrane Library, Scopus and Web of Science Core Collection databases was performed.ResultsOf 5,325 studies identified, 15 fulfilled our inclusion criteria. The studies which reported 2016 liver transplant recipients with de novo DSAs showed an increased complication risk, i.e. graft loss and chronic rejection (OR 3.61; 95% CI 1.94–6.71, P < 0.001; I2 58.19%), and allograft rejection alone (OR 6.43; 95% CI: 3.17–13.04; P < 0.001; I2 49.77%); they were compared to patients without de novo DSAs. The association between de novo DSAs and overall outcome failure was consistent across all subgroups and sensitivity analysis.ConclusionsOur study suggested that de novo DSAs had a significant deleterious impact on the liver transplant risk of rejection. The routine detection of de novo DSAs may be beneficial as noninvasive biomarker-guided risk stratification.